P–663 The ratio of serum progesterone (P4) to the number of follicles (P4/Follicle) is a more objective parameter for euploidy rate as compared to systemic progesterone. (6th August 2021) - Ab. ali, K; Lawrenz, B; Tegedor, A L; Ruiz, F R; El-Damen, A; Khatib, I. E; Fatemi, H; Munck, N. D
Abstract: Study question: Does the ratio of serum progesterone (P4) to the number of follicles (P4/Follicle) on the day of final oocyte maturation affect the ploidy status of the embryos? Summary answer: A high P4/Follicle ratio negatively affects the euploid rate of the embryos. What is known already: During ovarian stimulation, exogenous gonadotropins are administered to achieve multifollicular growth. Intense gonadotropin stimulation towards the end of the follicular phase seems to cause a premature progesterone rise in stimulated IVF cycles. The impact of serum progesterone elevation during the follicular phase has been studied intensively. Though most studies have focused on the effect of progesterone elevation on the endometrial receptivity, little is known about its possible impact on embryo development and ploidy status. The only study that investigated the effect of progesterone on the embryo ploidy status, was unable to show any significant impact. Study design, size, duration: This retrospective study was performed at ART Fertility Clinics Abu Dhabi, UAE and Muscat, Oman. All stimulation cycles (n = 975) were performed between January 2015 to December 2019 with patients aged between 18–45, Body mass index (BMI) of 18–35, stimulated either with rFSH or hMG. All embryos underwent ICSI and Preimplantation Genetic Testing for Aneuploidies (PGT-A), Patients with surgical sperm extraction, warmed oocytes or natural cycle IVF were excluded. Participants/materials, setting, methods: Serum P4 was measured on the last ultrasound prior triggering for final oocyte maturation. The P4/Follicle ratio was calculated as the ratio of P4 on trigger day to the number of follicles > 10 mm on the last ultrasound. Serum P4 and P4/Follicle ratio were then analyzed using linear and univariate regression model to find potential correlation with the number of oocytes retrieved, number of mature oocytes, embryo quality (day 3 and 5), and euploid rate. Main results and the role of chance: A total of 975 cycles were analyzed, with a mean age of 33.88±0.05 years, a mean BMI of 26.7±0.035 kg/m2. The mean number of oocytes collected was 12.53±0.058. Mean serum P4 on trigger day was 0.83±0.005 ng/ml and higher serum P4 values were observed as the number of oocytes retrieved and the number of mature oocytes increased (β = 0.026, p < 0.0001 and β = 0.028, p < 0.001, respectively). On the other hand, the mean P4/Follicle ratio was 0.056±0.00041 ng/ml and, unlike serum P4, the P4/Follicle ratio showed a negative correlation with the number of oocytes retrieved as well as with the number of mature oocytes (β=–0.001, p < 0.001 and β=–0.001, p < 0.001, respectively). While day 3 embryos were not affected by serum P4 or P4/Follicle ratio, the blastocyst quality was negatively affected by both increasing serum P4 levels and the P4/Follicle ratio (β=–0.012 p < 0.05, β=–0.002, p < 0.001, respectively). Euploid rates were positively correlated in cycles with increased serum P4 β = 0.18, p < 0.001), while negatively correlated in cycles with a high P4/Follicle ratio (β=–0.015, p < 0.001). After adjusting for potential confounders, only P4/Follicle remained as a significant negative factor for euploid rate (β=–0.004, p < 0.001, 95% CI: –0.007- –0.001, p < 0.001), which was not observed for serum P4 (p = 0.46). Limitations, reasons for caution: This is an observational study based on retrospective data; an improved extrapolation of the results might be obtained by performing a prospective study. Wider implications of the findings: The findings of this study should encourage clinicians to optimize the ovarian stimulation protocols not only based on serum P4, but also considering the P4/Follicle ratio. Trial registration number: Not applicable